Analisis Dan Simulasi Banjir Das Kenali Kecil Dengan Menggunakan Sig Dan Model Hidraulika Hec-Ras - Heri Muda Setiawan; Heri Junedi; Moch Zuhdi (Universitas Jambi, 2022)
Floods are the most common disasters in almost all places, including Indonesia and Jambi City in particular. Areas that are directly affected by the threat of flooding are in the Watershed. Kenali Kecil watershed is one of the sub- watersheds of Batanghari which is administratively located in Jambi City and Muaro Jambi Regency. The Kenali Kecil watershed is influenced by the rapid growth of Jambi City. Land conversion is not the only cause of flooding in the Kenali Kecil watershed. Floods also occur because the discharge/volume of water flowing in a river or drainage system exceeds its drainage capacity. This study analyzes the level of flood vulnerability based on SNI 8197:2015 and Head of BNPB Regulation No. 02 of 2012. The approach used in the SNI method is landscape analysis which emphasizes the process of forming natural systems on the earth's surface. Analysis of the level of flood vulnerability based on the Regulation of the Head of BNPB is based on the results of flood simulations using the HEC-RAS hydraulic model. The parameters used in this model are the manning’s coefficient, data geometry, discharge plan and terrain. The terrain used in this research is DEMNas. Discharge plan are obtained using the HEC-HMS application. In making the discharge plan, rainfall data for the last 10 years is needed, to get the CN and Impervious values, soil type maps and land use maps are needed. Based on the procedure of Indonesian National Standard (SNI) 8197:2015) the level of flood vulnerability in the Kenali Kecil watershed is in the medium level of 8.25 km2 (52.6%) and high level of 7.43 km2 (47.4%). Based on the HEC-RAS modeling for the 2-year return period (Q2), the flood area is 1.08 km2, the 5-year return period (Q5) is 1.2 km2 and the 10-year return period (Q10) is 1.3 km2. Based on the Regulation of the Head of BNPB No. 02 of 2012 the flood vulnerability level of the Kenali Kecil watershed is in the low level (<0.76) Q2 = 0.33 km2, Q5 = 0.31 km2, Q10 = 0.32 km2, medium level (0.76 – 1 ,5) Q2 = 0.32 km2, Q5 = 0.31 km2, Q10 = 0.34 km2 and high level (> 1.5) Q2 = 0.43 km2, Q5 = 0.58 km2, Q10 = 0.64 km2